prodquotpracsol

prodquotpracsol - Solutions to derivatives: f (x) = x2 −...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Solutions to derivatives: f (x) = x2 − 10x + 100 f (x) = 2x − 10 s(t) = t8 + 6t7 − 18t2 + 2t s (t) = 8t7 + 42t6 − 36t + 2 g (x) = x100 + 50x + 1 g (x) = 100x99 + 50 V (r) = 4 πr3 3 V (r) = 4πr2 F (x) = (16x)3 F (x) = 12288x2 G(y ) = (y 2 + 1)(2y − 7) G (y ) = 2y (2y − 7) + (y 2 + 1)2 √ −9 Y (t) = bt 10 x7 √ R (x) = −7 10x−8 1 x 1 g (x) = 2x − x2 g (x) = x2 + R(x) = Y (t) = −9bt−10 √ x+2 x−1 1 t− √ t 1 1 − 1/2 + 2 t−3/2 f (t) = 2 t h (x) = G(s) = (s2 + s + 1)(s2 + 2) H (t) = t(t + 2) y= G (s) = 4s3 + 3s2 + 6s + 2 H (t) = 1 t−2/3 (t + 2) + t1/3 3 y= √ x−1 y=√ x+1 √ √ ( x+1)( 1 x−1/2 )−( x−1)( 1 x−1/2 ) 2 2 √ y= ( x+1)2 y= f (t) = 1 y= y x4 + 3x2 + (4x = (−4 +x2+2x)2 x +1) y =A+ y= −B x2 B x + − 1 C x2 2C x3 √ 5 y = x + x2 2 y = 1 + 5 x − 3 /5 u= √ 3 √ t2 + 2 t3 u = 2 t−1/3 + 3t1/2 3 y= y= x x+ c cx (x+ x )−x(1− c ) x2 c ( x+ x ) 2 h(x) = f (u) = (x−1)−(x+2) (x−1)2 √ 3 f (u) = √ 1 − u2 1 + u2 (1+u2 )(−2u)−(1−u2 )(2u) (1+u2 )2 x2 + 4x + 3 √ x √ x(2x+4)−(x2 +4x+3)(1/2)x−1/2 x y = x 4/3 − x 2/3 5x √ y = 5 1 x − 1/2 2 y = 4 x 1/3 − 2 x − 1/3 3 3 y = x 2 + x + x −1 + x −2 y = ax2 + bx + c y = 2x + 1 − y= y= 1 x2 − 3t − 7 t2 2+ 5t − 4 (t +5t−4)(3)−(3t−7)(2t+5) (t2 +5t−4)2 √ y = x4 − 4 x 1 y = 4x3 − 4 x−3/4 √ v =x x+ 1 √ v= x2 x 3 1/ 2 x − 5 x − 7/2 2 2 y= ax + b cx + d y= 2 x3 a(cx+d)−c(ax+b) (cx+d)2 y = 2ax + b y= y= 4t + 5 2 − 3t 4(2−3t)−(4t+5)(−3) (2−3t)2 √ u=x 2 √ √ u = 2x 2−1 6 v=√ 35 t v = 6(− 5 t−8/3 ) 3 y= y= x5 x3 − 2 5x4 (x3 −2)−x5 (3x2 ) (x3 −2)2 ...
View Full Document

Ask a homework question - tutors are online